Electrostatic Interaction Between NS1 and Negatively Charged Lipids Contributes to Flavivirus Replication Organelles Formation - Ci, Yali; Yang, Yang; Xu, Caimin; Qin, Cheng-Feng; Shi, Lei (Frontiers in Microbiology, 2021)
Flavivirus replication occurs in membranous replication compartments, also known as replication organelles (ROs), which are derived from the host ER membrane. Our previous study showed that the nonstructural (NS) protein 1 (NS1) is the essential factor for RO creation by hydrophobic insertion into the ER membrane. Here, we found that the association of NS1 with the membrane can be facilitated by the electrostatic interaction between NS1 and negatively-charged lipids. NS1 binds to a series of negatively-charged lipids, including PI4P. A positively-charged residue, R31, located on the membrane-binding face of NS1 plays an important role in this interaction. The NS1 R31E mutation significantly impairs NS1 association with negatively-charged membrane and its ER remodeling ability in the cell. To interfere with the electrostatic interaction between NS1 and negatively-charged lipids, intracellular PIPs level was downregulated by the overexpression of Sac1 or treatment with PI3K and PI4K inhibitors, leading to the attenuation of flavivirus replication. Our findings emphasize the importance of electrostatic interaction between NS1 and negatively charged lipids in flavivirus RO formation.